1976
DOI: 10.1148/121.2.455
|View full text |Cite
|
Sign up to set email alerts
|

Local Control of Breast Cancer with Tumorectomy Plus Radiotherapy or Radiotherapy Alone

Abstract: 58 cases of breast cancer treated primarily by radiotherapy were evaluated to determine the optimum dose for local control. Of 36 patients with T1 + T2 lesions who had tumorectomy prior to radiotherapy, incomplete excision of tumor was demonstrated on microscopic examination in 18. The minimum tumor dose to the breast was 4,500 rads in 5 weeks. Treatment failed to control local tumor in only 2 (5%) and metastases in 1.26 (72%) remained disease-free for 2 to 9 years. Of the 22 patients with T3 + T4 lesions, tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…These findings were subsequently confirmed by other authors [11,13,15,18]. The vast majority of new disease manifestations were documented in areas distant from the irradiation fields and this led to the conclusion that most women with locally advanced breast cancer have indeed distant micrometastases at the time of diagnosis.…”
Section: Introductionsupporting
confidence: 69%
“…These findings were subsequently confirmed by other authors [11,13,15,18]. The vast majority of new disease manifestations were documented in areas distant from the irradiation fields and this led to the conclusion that most women with locally advanced breast cancer have indeed distant micrometastases at the time of diagnosis.…”
Section: Introductionsupporting
confidence: 69%
“…However, clinical follow‐up of our breast cancer patients showed a 10‐year relapse‐free survival rate of 96.9% (31) . The difference with the TCP found by Ghossein et al (29) (i.e., 93.4%) can be ascribed to the boost of 16 Gy, which is included in our clinical follow‐up. Poortmans et al (32) reported that the boost decreases the 10‐year local recurrence rate with 4%.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast, there is little knowledge on the reference dose distribution for TCP calculation, as the clinical follow-up study was performed before 1976. (29) In the 1960s and '70s, 3D treatment planning was very rare, and the first publications on the type-a (30) and the type-b (3) dose-calculation algorithms date from 1992 and 1989, respectively. During the clinical followup study, only the prescribed dose was known.…”
Section: E Aim 2: Determination Of Algorithm-specific Tcp and Ntcp Fmentioning
confidence: 99%
“…The reports came from the experience of single institutions such as the Harvard Joint Center, Yale University, Albert Einstein College of Medicine, the M. D. Anderson Cancer Center, and Princess Margaret Hospital in Toronto. [1][2][3][4][5] Six centers in France reported similar results at the American Radium Society Meeting in 1976. 6 This historic body of literature did not represent the first time breast conservation surgery had been used.…”
mentioning
confidence: 74%